Comparable results of autologous and allogeneic haematopoietic stem cell transplantation for adults with Philadelphia-positive acute lymphoblastic leukaemia in first complete molecular remission: An analysis by the Acute Leukemia Working Party of the EBMT. (June 2018) - Giebel, Sebastian; Labopin, Myriam; Potter, Michael; Poiré, Xavier; Sengeloev, Henrik; Socié, Gerard; Huynh, Anne; Afanasyev, Boris V.; Schanz, Urs; Ringden, Olle; Kalhs, Peter; Beelen, Dietrich W.; et al.
Abstract: Background: Allogeneic haematopoietic stem cell transplantation (alloHSCT) is considered a standard treatment for patients with Philadelphia chromosome–positive acute lymphoblastic leukaemia (Ph+ ALL) achieving complete remission after induction containing tyrosine kinase inhibitors (TKIs). Methods: We retrospectively compared results of myeloablative alloHSCT from either matched sibling donor (MSD) or unrelated donor (URD) with autologous (auto) HSCT for adults with Ph+ ALL in molecular remission, treated between 2007 and 2014. Results: In univariate analysis, the incidence of relapse at 2 years was 47% after autoHSCT, 28% after MSD-HSCT and 19% after URD-HSCT ( P = 0.0002). Respective rates of non-relapse mortality were 2%, 18%, and 22% ( P = 0.001). The probabilities of leukaemia-free survival were 52%, 55% and 60% ( P = 0.69), while overall survival rates were 70%, 70% and 69% ( P = 0.58), respectively. In multivariate analysis, there was a trend towards increased risk of overall mortality after MSD-HSCT (hazard ratio [HR], 1.5, P = 0.12) and URD-HSCT (HR, 1.6, P = 0.08) when referred to autoHSCT. The use of total body irradiation (TBI)–based regimens was associated with reduced risk of relapse (HR, 0.65, P = 0.02) and overall mortality (HR, 0.67, P = 0.01). Conclusion: In the era of TKIs, outcomes of myeloablative autoHSCT and alloHSCT for patients with Ph+ ALL in first molecular remission are comparable. Therefore, autoHSCT appears to be an attractive treatment option potentially allowing for circumvention of alloHSCT sequelae. Irrespective of the type of donor, TBI-based regimens should be considered the preferable type of conditioning for Ph+ ALL. Highlights: Comparable survival after autologous haematopoietic stem cell transplantation (autoHSCT) and allogeneic (allo) HSCT. Reduced risk of relapse after total body irradiation–based conditioning. AutoHSCT is a treatment option for patients with Philadelphia chromosome–positive acute lymphoblastic leukaemia in molecular remission.